Atomic structure and growth mechanism of T1 precipitate in Al–Cu–Li–Mg–Ag alloy. (December 2015) - Kang, Sung Jin; Kim, Tae-Hoon; Yang, Cheol-Woong; Lee, Je In; Park, Eun Soo; Noh, Tae Won; Kim, Miyoung
Graphical abstract: Abstract: The atomic structure of a 0.94-nm-thick T1 precipitate in an Al–Cu–Li–Mg–Ag alloy is investigated by combining aberration-corrected scanning transmission electron microscopy (STEM) and energy-dispersive X-ray spectroscopy (EDX). Ag segregates at the first layer of the T1 precipitate interface, revealing a significant compositional variation of Ag throughout the interface. Moreover, the T1 precipitate thickened from 0.94 nm with successive stacking of identical 0.94 nm thick layers.